PELATIHAN SISTEM PNEUMATIK DAN HIDROLIK UNTUK PENINGKATAN KOMPETENSI SISWA SMK BIDANG TEKNIK MESIN - Raihan Raihan; Anhar Khalid (Jurnal Pengabdian Masyarakat Berkelanjutan, 2025)
Pneumatic and hydraulic systems are technologies that are widely applied to industrial machinery and automation systems, so mastering them is an important competency for Vocational High School (SMK) students in the field of mechanical engineering. However, the limitations of practice-based learning cause students' understanding and skills of the system to be not optimal. This community service activity aims to improve the competence of vocational school students through applicable and practice-based pneumatic and hydraulic system training. The method of implementing activities includes the preparation stage, the implementation of training through lectures and direct practice, and the evaluation of training results. The results of the activity showed an increase in students' understanding of the basic concepts, components, and working principles of pneumatic and hydraulic systems. In addition, students' practical skills in assembling and operating systems have also improved. This training makes a positive contribution to increasing the readiness of vocational school students to face the needs of the industrial world and supports the strengthening of vocational education through synergy between universities and vocational schools.